The Role of Government and NGO in Promoting Wellness of People with Down Syndrome - Yeo Kee Jiar; Lina Handayani; Lu Xi (Institute of Advanced Engineering and Science, 2014)
People with Down Syndrome (PWDS) experience cognitive delays indicated by difficulties with cognition, long-term memory and non-verbal problem solving skills. PWDS have specific speech and language impairments which affect all aspects of development. Some children develop difficult behaviors which cause family stress and affect social and educational inclusion. These deficits are worsened by a higher incidence of certain medical problems which were extensive from birth to old age. Being intellectually challenged, PWDS face many challenges and barriers to care for themselves, to lead rich and varied lives as well as to get involved in all aspects of community life. Besides helping them to assume responsibility for their own wellbeing, it is upon dedications from all parties to assist them to live a longer life expectancy with dignity and wellness intact. This paper aims to understand the scope of wellness for PWDS and the hindering factors as well as identifying contributions towards wellness of PWSD, its flaws and suggestions for improvement. The analysis and discussion is grounded in the context of Malaysia against the backdrop of PWDS across nations. This paper concludes that People with Disabilities (PWD) in Malaysia are protected by different laws and Acts. Many services are provided by government and NGO but these provisions do not benefit PWDS as much as their disabled peers who are not intellectually challenged. Job opportunities and total wellness especially after finishing the basic schooling seems quite bleak for PWSD due to their obvious cognitive delays and adaptive behaviors.DOI: http://dx.doi.org/10.11591/ijere.v3i3.6453